Novel pranoprofen‐poly(ε‐caprolactone) conjugates: microwave‐assisted synthesis and structural characterization. Issue 5 (26th October 2020) - Impallomeni, Giuseppe; Mineo, Placido Giuseppe; Vento, Fabiana; Ballistreri, Alberto
Abstract: Biodegradable polymers are used in many biomedical devices, such as implants, cellular scaffolds and drug delivery systems. To improve drug delivery capability and to reduce systemic toxicity, the interest in polymer–drug conjugates has increased remarkably. With this aim, pranoprofen (PPF) (an effective non‐steroidal anti‐inflammatory drug used mainly in ophthalmology) was conjugated to poly(ε‐caprolactone) (PCL) via microwave‐assisted transesterification, acid‐catalyzed by p ‐toluenesulfonic acid. The products obtained were characterized by NMR, matrix assisted laser desorption ionization time of flight mass spectrometry, gel permeation chromatography (which gave proof of the covalent link between PPF and PCL) and thermal analyses. The conjugates were found to contain up to 4.3% w/w of PPF and had molecular weights ranging from 5 to 12 kDa. © 2020 Society of Industrial Chemistry Abstract : Pranoprofen was conjugated to poly(ε‐caprolactone) via microwave‐assisted transesterification, acid‐catalyzed by p ‐toluenesulfonic acid. The products were found to contain up to 4.3% w/w of pranoprofen and had molecular weights ranging from 5 to 12 kDa.